Reductions in Drinking Predict Increased Distress: Between‐ and Within‐Person Associations between Alcohol Use and Psychological Distress During and Following Treatment. (16th October 2020) - Levine, Jacob A.; Gius, Becky K.; Boghdadi, George; Connors, Gerard J.; Maisto, Stephen A.; Schlauch, Robert C.
Abstract : Background: As the nature of the association between alcohol use disorder (AUD) and other disorders is not well understood, the ways in which psychological distress changes during the course of treatment for AUD are relatively unknown. Existing literatures posit 2 competing hypotheses such that treatment for AUD concurrently decreases alcohol use and psychological distress or treatment for AUD decreases alcohol use and increases psychological distress. The current study examined the ways in which psychological distress changed as a function of treatment for AUD, including the relationship between psychological distress and drinking behaviors. Methods: Secondary data analysis was conducted on an existing clinical trial dataset that investigated the effect of cognitive–behavioral therapy and therapeutic alliance feedback on AUDs. Specifically, data collected at baseline, posttreatment, 3‐month, 6‐month, 9‐month, and 12‐month follow‐up assessments were examined. Results: Results indicated decreases in heavy drinking days, increases in percentage of days abstinent, and decreases in overall psychological distress. Findings also revealed that changes in psychological distress did not predict changes in drinking at the next time interval; however, decreases in drinking predicted higher psychological distress at the next assessment. Further, average levels of psychological distress were positively associated with rates of drinking. Conclusions: The current study provides some insight into how psychological distress changes during the course of treatment for AUD, including the relationship between changes in drinking and such symptoms. Future research should continue to explore these relationships, including the ways in which treatment efforts can address what may be seen as paradoxical effects. Abstract : The current study sought to better understand both within‐ and between‐person associations between alcohol consumption and psychological distress over 12 months following cognitive behavioral treatment for alcohol use disorder. Our findings indicated that while within‐person reductions in drinking predicted increases in psychological distress, changes in psychological distress did not affect alcohol consumption. Between‐person psychological distress was associated with alcohol consumption, such that those with greater distress consumed more alcohol on average.